Bridging Traditional ITSM and Modern Engineering: An Ethnographic Study of ITIL & SRE on GCP - Gedela, Kranti Kiran Kumar (Digital Repository of Theses - SSBM Geneva, 2025)
This research explores how large-scale organizations using ITIL as their primary ITSM framework can effectively work with vendors and partners using Google’s SRE. Through case studies, it examines the synergy of formal process management and automation-driven reliability practices, highlighting key challenges related to resource allocation, cultural misalignment, and tooling complexities. The findings demonstrate the importance of bridging ITIL’s robust governance and SRE’s adaptive engineering mindset to enhance service resilience, reduce downtime, and achieve faster innovation. The study introduces practical frameworks for incident management, communication protocols, and continual improvement, emphasizing specialized metrics such as SLAs, SLOs, and error budgets. By synthesizing empirical data and theoretical reflections, it provides a roadmap for hybrid operational models that align business-critical IT processes with next-generation reliability engineering. In essence, this dissertation underscores the strategic imperative of fusing ITIL and SRE to foster operational excellence and secure competitive advantage in rapidly evolving digital environments.